Annexin A1 and the Resolution of Inflammation: Modulation of Neutrophil Recruitment, Apoptosis, and Clearance - Michelle Amantéa Sugimoto; Juliana Priscila Vago; Mauro Martins Teixeira; Lirlândia Pires Sousa (Journal of Immunology Research)
Neutrophils (also named polymorphonuclear leukocytes or PMN) are essential components of the immune system, rapidly recruited to sites of inflammation, providing the first line of defense against invading pathogens. Since neutrophils can also cause tissue damage, their fine-tuned regulation at the inflammatory site is required for proper resolution of inflammation. Annexin A1 (AnxA1), also known as lipocortin-1, is an endogenous glucocorticoid-regulated protein, which is able to counterregulate the inflammatory events restoring homeostasis. AnxA1 and its mimetic peptides inhibit neutrophil tissue accumulation by reducing leukocyte infiltration and activating neutrophil apoptosis. AnxA1 also promotes monocyte recruitment and clearance of apoptotic leukocytes by macrophages. More recently, some evidence has suggested the ability of AnxA1 to induce macrophage reprogramming toward a resolving phenotype, resulting in reduced production of proinflammatory cytokines and increased release of immunosuppressive and proresolving molecules. The combination of these mechanisms results in an effective resolution of inflammation, pointing to AnxA1 as a promising tool for the development of new therapeutic strategies to treat inflammatory diseases.